2018
DOI: 10.1186/s12889-018-6182-2
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the last polio sanctuaries with Directly Observed Oral Polio Vaccination (DOPV) in northern Nigeria, (2014–2016)

Abstract: BackgroundThe declaration of poliomyelitis eradication as a programmatic emergency for global public health by the 65th World Health Assembly in 2012 necessitated innovations and strategies to achieve results. Review of the confirmed polio cases in 2013 showed that most of the cases were from non-compliant households, where parents connived with vaccinators to finger mark the children without actually vaccinating the children with oral polio vaccine or children were absent from home at the time of the visit of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…This creates room for pockets of populations without OCV protection, thus risking cholera outbreaks. Given the history of vaccine hesitancy in Borno, 38 we agree with Luquero et al 39 that qualitative studies are needed to access the behavioural determinants of OCV acceptability in Borno in a preemptive context. Data of administrative coverage were 105% and 99% during first and second rounds, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…This creates room for pockets of populations without OCV protection, thus risking cholera outbreaks. Given the history of vaccine hesitancy in Borno, 38 we agree with Luquero et al 39 that qualitative studies are needed to access the behavioural determinants of OCV acceptability in Borno in a preemptive context. Data of administrative coverage were 105% and 99% during first and second rounds, respectively.…”
Section: Discussionmentioning
confidence: 52%
“…The relationship between good monitoring and smooth implementation of mass vaccination has been established in other countries, namely Pakistan and Nigeria. 33 , 34 Furthermore, campaign monitoring provides a platform for intellectual interaction with updated information. The State Health Department constantly monitored the progress of SIAs and provided technical guidance whenever necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Although -as the summary table in Appendix 4 makes clear -the vast majority of studies referenced community engagement as a trust-building measure to a greater or lesser degree, four studies explicitly focusing on this aspect met the inclusion criteria for the review, all of which concerned multi-dimensional community mobilisation activities (68)(69)(70), and one of which combined community mobilisation activities with direct observation of polio vaccination by officials to ensure proper administration of vaccination (71). All four were implemented in Nigeria, and most were concerned with improving polio vaccination uptake.…”
Section: Demand-side Interventions: Community Engagement and Mobilisa...mentioning
confidence: 99%
“…Study outcomes focused predominantly on measures of administrative coverage and missed opportunities for vaccination. Three of the studies relied on narrative assessments of impact without formal statistical testing (68)(69)(70); the final study presented a rudimentary time series analysis (71). Two of the four studies found declines in the proportion of children who had not received any OPV doses during the study period (68,71); another showed concurrent, large increases in pentavalent vaccination coverage from an integrated intervention designed to improve uptake in hard-to-reach communities in Northern Nigeria (70), albeit with marked variations across geographies.…”
Section: Demand-side Interventions: Community Engagement and Mobilisa...mentioning
confidence: 99%